Rekonstruksi Amar Ma’ruf Nahi Munkar sebagai Paradigma Konseling Profetik-Emansipatoris: Fondasi Teoretis Masyarakat Non-Kekerasan - Dita Nabila; Elfita Fitriani; Muhamad Ulul Azmi; Ali Hasan Siswanto (Jurnal Teologi Islam, 2026)
This article departs from the escalating reality of violence in contemporary society, which manifests not only in physical forms but also in structural, symbolic, and digital dimensions that operate systemically and are often legitimized within social practices, including religious discourses. Although the concept of non-violence has been widely discussed across disciplines, existing approaches remain largely normative and have yet to provide an operational framework that integrates theological, psychological, and social dimensions. The research gap lies in the absence of a conceptual formulation that reconstructs amar ma’ruf nahi munkar as a transformative method capable of addressing the problem of violence in a holistic manner. This study employs an integrative theoretical approach that combines prophetic theology, critical social theory, and counseling psychology. The research method is qualitative with a philosophical-critical orientation, utilizing hermeneutic analysis of religious texts alongside critical discourse analysis of contemporary academic literature. This approach enables a contextual reinterpretation of Islamic normative concepts while critically engaging with the surrounding social realities. The main argument of this article asserts that amar ma’ruf nahi munkar should be reconstructed as a Prophetic-Emancipatory Counseling paradigm—namely, a dialogical, reflective, and transformative process aimed at fostering critical consciousness at both individual and collective levels in order to transform structures of violence. This paradigm integrates divine values (prophetic dimension), emancipatory awareness (critical liberation), and dialogical practice (counseling) into a coherent and operational framework.The scientific contribution of this article lies in the development of a novel conceptual paradigm that bridges spirituality, psychology, and social theory in the pursuit of a non-violent society. The novelty of this study resides in the reinterpretation of amar ma’ruf nahi munkar as an emancipatory and applicable form of social counseling, making it relevant for addressing the complexities of violence in modern society.